Technological innovation in Small and Medium Enterprises: A bibliometric analysis - Roni Budianto; Agung Praptapa; Eliada Herwiyanti; Puji Puji; Eko Suyono; Oman Rusmana (Journal of Sustainable Tourism and Entrepreneurship, 2022)
Purpose: The objective of this study is to find out the development of SMEs in the digital era. Research Methodology:  The authors used the Scopus database and searched for articles containing keywords such as "technolog* innovation" AND smes OR "small and medium enterprises." The data were obtained from 1990 to 2023, with a total of 408 documents consisting of 295 articles, 20 book chapters, 67 conference papers, 8 conference reviews, 1 erratum, 1 note, 5 retracted documents, and 11 review documents. Results: The study found that the development of publications on technological innovation in SMEs experienced fluctuations, but tended to increase. The most productive source and the most impactful author were IEEE Transactions on Engineering and Management, and the majority of publications were conducted in collaboration with fellow authors from the same country. The most cited country was the United Kingdom, followed by Singapore and the United States. The topic that appeared most often in publications was related to technological innovation. Contributions: This study highlights the importance of technological innovation in SMEs and its impact on the economy.